Development of a reactive distillation column prototype to convert acrylic acid in the petrochemical wastewater to valuable butyl acrylate through esterification - Chin, Sim Yee; Anwaruddin, Hisyam; Mohamad Rizza, Othman; Sumaiya, Zainal Abidin @ Murad (2015)
Wastewater containing 2-20wt% of acrylic acid (AA) is currently burned using incinerator which is neither economical feasible nor environmental friendly. Esterification in a reactive distillation column (RDC) is a promising method to recover AA from wastewater. AA could be converted to a valuable ester product while purifying water. A RDC prototype was developed and tested for the recovery of AA from the wastewater. A maximum AA conversion of 99.5% was achieved when the BuOH to AA molar ratio and reflux ratio were 4 and 5 respectively. The data was used to validate the simulation results generated using equilibrium stage model in ASPEN PLUS program. A technically optimized RD process was then proposed.